The Development of Solar Powered Portable Mini NFT Aquaponics Educational Kits - Tengku Ahmad, Tengku Muhammad Syukri; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2022)
Aquaponics has been introduced as a subject as a subtopic in Rekabentuk Dan Teknologi (RBT) in order to expand the usage of aquaponics in the community. However, the lack of learning material is an issue since there is no hands-on experience for the students. From this issue, it has to come out with one of the innovations to develop mini NFT aquaponics educational kits. This project aims to develop a prototype of a mini aquaponics system that can be used as a proper learning material to fulfill the student’s needs. This aquaponics system was powered by using solar photovoltaics and batteries, which could avoid use on the grid power supply. This could save bills since the system should be run for 24 hours non-stop. The solar-powered NFT aquaponics system could not only introduce aquaponics system, but also renewable energy to the students.